Can Sport Education improve attitudes towards secondary Physical Education? - Morales-Ortiz, Esther; Burgueño, Rafael; Cueto-Martín, Belén; Macarro-Moreno, José; Medina-Casaubón, Jesús (Universidad Autónoma de Madríd, 2021)
The objective of this research was to examine the influence of a Sport Education season on students’ attitudes towards Physical Education (PE). The participants were 53 (31 male and 22 female; Mage = 15.13, SDage = 1.40) secondary school students who took part in a Sport Education intervention consisting of fourteen 55-minute sessions. A quasi-experimental design with no control group and with pre-test and post-test measures was adopted. The results derived from MANOVA test showed a significant increase in the levels of perception of PE and the teacher, difficulty of PE, usefulness of PE and preference for PE in students after a Sport Education season. No significant multivariate effects were found for age, gender or after-school sport. These findings are discussed highlighting the importance of Sport Education in the development of the students’ attitudes towards PE as a means to promote their comprehensive education.
¿Puede la Educación Deportiva mejorar las actitudes hacia la educación física en secundaria?
Keywords: Educación física - Estudio y enseñanza; Investigación activa en educación; Model-based practice; Pedagogical models; Physical education teaching; Attitudinal domain; Curriculum and teaching